Clean Water Treatment Training and Its Relation to Organ Damage Prevention at Al-Jihad Islamic Boarding School - Veterini, Lysa; Salim, Hotimah Masdan; Bintarti, Tri Wahyuni; Muhammad, Akbar Reza; Choiriya, Dian Dakwatul (UKInstitute, 2026)
Access to clean water in Indonesia remains a challenge, especially in rural areas and educational environments such as Islamic boarding schools. Consuming contaminated air in the long term from shallow wells can cause damage to organs, such as the kidneys, liver, and digestive tract. Therefore, the availability of sufficient and affordable clean water is very important for the survival and well-being of society. The approach in the Islamic boarding school environment, through community service activities and conducting counseling related to clean water processing and its relationship to preventing organ damage, is very important to create collective awareness in maintaining the availability of clean water. The implementation was carried out on May 17, 2025, at the Al-Jihad Islamic Boarding School in Surabaya. The series of activities began with filling out a pre-test, counseling through interactive lectures, and then continued with filling out a post-test to transmit the students' understanding after participating in this activity. The activity showed an increase in students' knowledge about water quality (management) and its impact on health (p0.05). Providing counseling to students at the Al Jihad Islamic Boarding School in Surabaya was able to increase students' knowledge about water quality (management) and its impact on health.